2011
DOI: 10.3945/ajcn.110.001156
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress and antioxidant supplementation in pregnancy disorders

Abstract: Oxidative stress is widely implicated in failed reproductive performance, including infertility, miscarriage, diabetes-related congenital malformations, and preeclampsia. Maternal obesity is a strong risk factor for preeclampsia, and in a recent study we observed oxidative stress in the oocytes of obese animals before pregnancy as well as in early-stage embryos. This adds to the growing evidence that investigators need to focus more on the preconceptual period in efforts to prevent pregnancy disorders, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
141
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 59 publications
4
141
0
5
Order By: Relevance
“…In the same study, an increase in oxidative stress biomarkers, such as MDA and lipid peroxides, was observed in placental tissue from early pregnancy losses compared with controls, despite upregulation of antioxidants such as catalase, glutathione peroxidase, and Cu/Zn and Mn superoxide dismutase. The authors suggested that increased ROS may result from a premature and abrupt establishment of maternal placental perfusion (Poston et al 2011). By contrast, other studies also suggested that the oxidative damage to the trophoblast induced by premature and widespread onset of the maternal placental circulation is a key factor in early pregnancy loss, but the premature oxidative stress increase was concluded to result from the lack of antioxidant levels to neutralize the increased levels of ROS (Burton and Jauniaux 2011;Jauniaux et al 2003;Myatt and Cui 2004).…”
Section: Spontaneous Miscarriage and Recurrent Pregnancy Lossmentioning
confidence: 83%
See 4 more Smart Citations
“…In the same study, an increase in oxidative stress biomarkers, such as MDA and lipid peroxides, was observed in placental tissue from early pregnancy losses compared with controls, despite upregulation of antioxidants such as catalase, glutathione peroxidase, and Cu/Zn and Mn superoxide dismutase. The authors suggested that increased ROS may result from a premature and abrupt establishment of maternal placental perfusion (Poston et al 2011). By contrast, other studies also suggested that the oxidative damage to the trophoblast induced by premature and widespread onset of the maternal placental circulation is a key factor in early pregnancy loss, but the premature oxidative stress increase was concluded to result from the lack of antioxidant levels to neutralize the increased levels of ROS (Burton and Jauniaux 2011;Jauniaux et al 2003;Myatt and Cui 2004).…”
Section: Spontaneous Miscarriage and Recurrent Pregnancy Lossmentioning
confidence: 83%
“…So, evidence from this review does not support routine antioxidant supplementation during pregnancy to reduce the risk of PE and other complications in pregnancy (Poston et al 2011;Ruder et al 2008). …”
Section: Intrauterine Growth Restrictionmentioning
confidence: 99%
See 3 more Smart Citations